Penggunaan Film Dokumenter Sejarah Belangkaet Sebagai Media Pembelajaran Sejarah di Kelas XI IPS 2 SMAN 1 Simpang Hilir - Shelli Shelli; Andang Firmansyah; Astrini Eka Putri; Rustiyarso Rustiyarso; Haris Firmansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This observe goals to determine the usage of teachers in using the media documentary movie records beangkaet in gaining knowledge of history, the planning process, instructor implementation in the use of documentary film media records belakkaet in studying history, and the limitations felt via the teacher inside the use of historic documentary movie media beangkaet on gaining knowledge of history, in magnificence XI IPS 2. The research method used is descriptive with a shape of qualitative studies. The facts assets for this research had been history instructors and students class XI IPS 2. The region of this research is at SMAN 1 Simpang Down circulate that's on Jalan Pramuka, Teluk Melano, Kec. Simpang Downstream information series strategies used are commentary, interviews and documentation while the information collection gear are statement sheets, interview courses, and documentation. data evaluation strategies researchers use information discount, presentation statistics and drawing conclusions. to test the validity of the facts researchers use triangulation. From the outcomes of data evaluation researchers understanding that: (1) For planning using film history of belangkaet documentaries as a medium for learning history, instructors additionally have to prepare the steps education of gaining knowledge of implementation plans (RPP) for adapt to the getting to know fabric as a way to be brought to college students. (2) Implementation of use belangket ancient documentary films as gaining knowledge of media history.(three) within the use of ancient documentary film media belakaet often instances we find some barriers that turn out to be a problem in a studying manner both in terms of technical or non-technical.